2005
DOI: 10.1007/s11910-005-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome

Abstract: Restless legs syndrome is a very common and still under-diagnosed neurologic condition that can cause severe morbidity. The pathology centers around central nervous system iron homeostatic dysregulation with subsequent alterations in dopaminergic functioning. Genetic studies will hopefully soon identify specific abnormalities. Treatment of restless legs syndrome with dopaminergic medications is highly effective, although augmentation may occur eventually and require dosing flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 98 publications
1
32
0
Order By: Relevance
“…This result is in agreement with Ondo (2015) who reported that leg cramps symptoms are generally worse in the evening & at night (35) . Moreover, kanaan and Sawaya (2001) stated that leg cramps commonly happen at night where the plantar flexed foot places the calf, ventral foot muscles in the most shortened and (36) .…”
Section: Effect Of Reflexology Foot Massage On Leg Cramps For Patientsupporting
confidence: 92%
“…This result is in agreement with Ondo (2015) who reported that leg cramps symptoms are generally worse in the evening & at night (35) . Moreover, kanaan and Sawaya (2001) stated that leg cramps commonly happen at night where the plantar flexed foot places the calf, ventral foot muscles in the most shortened and (36) .…”
Section: Effect Of Reflexology Foot Massage On Leg Cramps For Patientsupporting
confidence: 92%
“…In most cases, serum ferritin and iron-binding saturation should be obtained for serum iron deficiency, and electrolytes should be obtained for renal failure 5 . Familial cases of RLS demonstrating autosomal dominant pattern of inheritance are well-know described.…”
mentioning
confidence: 99%
“…Long-term studies of RLS treatment outcomes have focused primarily on effects of medication [32][33][34][35][36][37][38] , but the findings have been inconsistent. Whereas some studies have reported a marked decrease in RLS [37] and outstanding efficacy of RLS-related medication [32] , others have reported an increase in symptoms [35] , or only symptomatic relief rather than any curative effect [32] .…”
Section: Discussionmentioning
confidence: 99%